PERSEPSI ALUMNI PROGRAM STUDI AKUNTANSI MENGENAI KECERDASAN EMOSIONAL DAN KECERDASAN INTELEKTUAL TERHADAP SIKAP ETIS (STUDI PADA ALUMNI PROGRAM STUDI AKUNTANSI UNIVERSITAS PENDIDIKAN INDONESIA) - Riska Indri Oktaviani, - (2022)
This study aims to determine the effect of emotional intelligence and intellectual intelligence on ethical attitudes based on the perceptions of alumni of the accounting study program. The population in this study were all alumni of the accounting study program at the Indonesian Education University. By using quantitative research methods and surveys as data collection techniques, namely by distributing questionnaires to respondents. The respondents who were sampled in this study were all alumni of the accounting study program who had work experience and had expertise in finance with a total of 34 respondents. The data obtained were tested by correlation test and significance test. The results of this study indicate that the H1 hypothesis is rejected, because this study found a significant positive relationship between emotional intelligence and the ethical attitudes of alumni of the accounting study program. Hypothesis H2 is accepted because in this study it was found that intellectual intelligence does not have a significant relationship with the ethical attitudes of alumni of the study program. And the research results from the hypothesis H3 that emotional intelligence and intellectual intelligence together have a significant relationship to the ethical attitude of alumni of the accounting study program. Suggestions for further researchers are expected to be able to add other factors outside of this study, which are more influential on ethical attitudes. Keywords: Emotional Intelligence, Intellectual Intelligence, Ethical Attitude.